DETERMINATION OF PREMIUMS IN RETURN FREIGHT INSURANCE FOR ONLINE RETAIL IN GERMANY - Huang, Keith
The growth of mobile technology and e-commerce has significantly transformed the retail industry in recent years. E-commerce is anticipated to account for more than 50% of all retail sales during the next ten year. Product returns are one of the biggest problems e-tailers confront, especially in German online transactions. In Germany, one out of every four online purchases is returned each year, which has an adverse effect for e-tailers because of the costs associated with returns. In order to address this issue, return freight insurance potential to boost e-tailer profitability and transfer return obligation from e-tailers to consumers in the German market will be investigated. Transactional data from the German shoe market's online retailers is utilized to evaluate the effect of return freight insurance. To assess the effect of return freight insurance, two consumer utility models based on Chen (2017) were used. Both models investigate e-tailers' demand and earnings in two different situations: without return freight insurance (Scenario N) and with return freight insurance (Scenario I). The findings suggest that return freight insurance can raise e-tailer profitability by increasing consumer demand since its beneficial effects balance the price rise brought on by the payment of the premium. As a result, return freight insurance may be a viable solution to begin the shift to a better customer culture and to reduce seller losses brought on by return expenses.